A Critical Discourse Analysis on Bvrtanâ€™s Persatvan Rakyat Svkatani - Petrik Mahisa Akhtabi (Universitas Airlangga, 2023)
Bvrtan is a quite unique Indonesian black metal band. Combining humor with the black metalâ€™s dark aesthetic, Bvrtanâ€™s works have been well appreciated by the Indonesian underground scene. In contrast to other black metal practices that shout anti-religion and absolute freedom messages, Bvrtanâ€™s works are identical with social criticism of Indonesian agrarian context. Thus, this study exists to discuss one of Bvrtanâ€™s work entitled Perstavan Rakyat Svkatani. By applying theoretical approach of Faircloughâ€™s critical discourse analysis, the researcher uncovers how Bvrtanâ€™s work is composed of various type of texts, ranging from linguistic, the discursive practice and social contexts. By the theoretical view, the researcher finally found that this work specifically relate to a wider context of Indonesian agrarian problem that involves the pseudo-welfare of farmers. With satirical lyrics and angry expletives, the phrase of â€œsejahtera matamvâ€ is the pivotal key to understand every dimension of discourse within this work. Â